Kecerdasan Emosional dan Hubungannya dengan Stres Kerja pada Pekerja Bagian Maintenance di Industri Asam Fosfat - Dandi Widhi Ramadhan; Dayinta A Syaiful; Yustinus Denny Wahyudiono; Indriati Paskarini; Putri Ayuni Alayyanur; Deanida Ankhofiya (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Every workplace has potential hazards, one of which is psychological hazards, namely work stress. The stress felt by workers can interfere with their work activities if not controlled immediately. Job stress can be caused by various factors. The purpose of this study is to analyze the relationship emotional intelligence with work stress on maintenance workers at PT X. This research is expected to be able to contribute to the achievement of SDGs (sustainable development goals) number 3, namely health and well-being for all ages including workers. The purpose of this study was to analyse the relationship between emotional intelligence with work stress on maintenance workers at PT X. This research is included in quantitative research with the type of observational research with a cross-sectional approach. The population in this study were all maintenance workers at PT X, amounting to 35 people. The sampling technique used is the total population. The independent variables in this study include emotional intelligence. While the dependent variable is work stress. The method of data collection is using a questionnaire. The results of the data that have been collected are statistically analyzed using the Spearman correlation test and the Cramer contingency coefficient correlation test. The results showed that emotional intelligence has a low relationship (r= -0,291) with work stress and has the opposite direction of relationship. The conclusion of this study is that the higher the emotional intelligence, the lower the perceived work stress. Therefore, the company can reduce work stress by knowing the causes of the mental workload of workers and increasing emotional intelligence by providing case studies, puzzles, etc. during the safety morning talk.Keywords: mental workload, emotional intelligence, work stress